Curcumin ameliorates doxorubicin‐induced cardiotoxicity by abrogation of inflammation, apoptosis, oxidative DNA damage, and protein oxidation in rats. Issue 2 (5th January 2018) - Benzer, Fulya; Kandemir, Fatih Mehmet; Ozkaraca, Mustafa; Kucukler, Sefa; Caglayan, Cuneyt
Abstract: Doxorubicin (DXR) is a highly effective drug for chemotherapy. However, cardiotoxicity reduces its clinical utility in humans. The present study aimed to assess the ameliorative effect of curcumin against DXR‐induced cardiotoxicity in rats. Rats were subjected to oral treatment of curcumin (100 and 200 mg/kg body weight) for 7 days. Cardiotoxicity was induced by single intraperitoneal injection of DXR (40 mg/kg body weight) on the 5th day and the rats sacrificed on 8th day. Curcumin ameliorated DXR‐induced lipid peroxidation, glutathione depletion, decrease in antioxidant (superoxide dismutase, catalase, and glutathione peroxidase) enzyme activities, and cardiac toxicity markers (CK‐MB, LDH, and cTn‐I). Curcumin also attenuated activities of Caspase‐3, cyclooxygenase‐2, inducible nitric oxide synthase, and levels of nuclear factor kappa‐B, tumor necrosis factor‐α, and interleukin‐1β, and cardiac tissue damages that were induced by DXR. Moreover, curcumin decreased the expression of 8‐OHdG and 3, 3′‐dityrosine. This study demonstrated that curcumin has a multi‐cardioprotective effect due to its antioxidant, anti‐inflammatory, and antiapoptotic properties.